The Influence of Funding Decisions, Dividend Policies, and Market Value on Firm Value with Profitability as an Intervening Variable in Consumer Non-Cyclicals Listed on the Indonesian Stock Exchange - Winda Sibleni; Dedi Hariyanto; Heni Safitri (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to look at the influence of funding decisions, dividend policy, and market value on firm value with profitability as an intervening variable on consumer non-cyclical companies listed on the Indonesia Effectssa. The results of the path analysis obtained equation 1: Z = 8,345 - 2,856 X1 - 0.001 X2 + 1,226 X3 and equation 2: Y: 837,156 - 0.004 X1 + 8,862 X2 + 5,010 X3 + 93,745 Z. The results of the correlation coefficient test (R) show that the variables of financing decisions, dividend policy and market value have a very weak relationship with the profitability variable, while the variables of financing decisions, dividend policy, and market value on the variable of firm value with profitability as the intervening variable have a fairly strong relationship. The t-test results show that the funding decision variable, dividend policy and market value do not have a partial effect on profitability and the dividend policy variable with profitability as an intervening variable partially affects the firm value, while the funding decision and market value through profitability as intervening variables do not have a partial effect on the firm value. For further research, it is advisable to include additional variables, such as corporate governance, management decisions, market conditions, or investor sentiment, to provide a more in-depth understanding of the factors that influence firm value.